On the Teachers’ Homunculus established in our Minds - Litvinaitė, Jūratė (Acta Paedagogica Vilnensia, 2019)
[full article and abstract in Lithuanian; abstract in English] There is a clear notion in society of what is a “real teacher”; there are many discourses describing in detail the kind of a teacher that is considered good, how one should look and behave, and what is good “teaching.” This knowledge did not come from a deep psychological recognition of the teachers or their personal traits; it is simply a constructed set of traits and behaviors that need to be mastered by a person striving to become a teacher. A teacher must match a teacher’s homunculus. This is a newly introduced notion in education sociology, constructed on the basis of the notion of a sociological homunculus, proposed by the sociologist Zenonas Norkus (1996). The teacher’s homunculus is described as a historically and virtuously formed sociological construct that universally describes the concept of a teacher rooted in the society – a standard of a sort, the meeting of which legitimizes a teacher’s work. The teacher’s homunculus rises as a common image that includes all teachers and combines their various practices; it blossoms in the mundane speech and is used as the standard of evaluation of the teachers’ work: “all teachers are the same,” “you know a teacher when you see one” etc. It also finds its way to the consciousness of the teachers themselves, like a screenplay of their professional work and behavior, like a role that has a historical tradition prescribed to them by society. How the image of a teacher – this homunculus – Is created in the consciousness of other social agents, how it pierces through to the teachers’ concepts of themselves – all of this was very widely analyzed by the representatives of the “new education sociology.” The authors discussed in this article – P. Bourdieu, P. Brown, P. Trowler and A. Luke – found the positions of agents from other fields toward teachers. The insights and reasoning of the sociologists revealed that other social agents see the teachers only as an executant of certain functions, a “marionette” – a homunculus without a will. The construct of the teacher’s homunculus is also characteristic to the participants of educational field and to the teachers themselves. As the abovementioned sociologists discovered, the teacher’s image – one’s look, behavior, views, lifestyle – are conservative and deeply rooted into the consciousness of various social agents. A person ready to become a teacher has to gain not only the credentials giving the right to teach but a place of work and the look that will represent him or her. It is, first and foremost, the acknowledgement of others of you as a teacher (Alsup, 2008). The features of a teacher’s look, behavior and style are heavily shaped by the popular culture. Pre-school children already have a clear vision of how their teachers will look and behave. Research shows that this expectation motivates teachers to construct a corresponding image (Weber, Mitchell, 2003). Speech is one of the distinctive features of a teacher. Yet speech is not the content being said; it is a means by which relations are created and fulfilled (Bernstein, 1996). The teacher’s homunculus is also perceived as full of discipline – one always abides by the rules and seeks that everyone else does the same (Foucault, 1998). It is revealed in this study that a teacher’s image and the functions prescribed to a teacher – the notion of a teacher’s homunculus – impact the teachers’ concepts of themselves, their positions in the field of education and the behavior and views toward teachers shared by other agents of society. Z. Norkus (1996) has said that a homunculus is described based on the expectations of a society; one’s image becomes a part of an identity and constructs the role that one plays. Empirical research was carried out to analyze how all this appears in practice. This article presents the results of qualitative study carried out using the role-construction method. The research was carried out during 2017–2018; 21 informants, 16 teachers who used to or still are teaching in schools around Lithuania, and 5 principals took part in this research. Almost all participants admitted that “outside” forces have the most impact on the teachers’ concepts of themselves and their professional work. Research shows that a teacher feels as if unable to avoid being put under control, because the teacher is an easily recognizable homunculus and always feels the demand to be prepared for control and assessment by other agents in the environment. Most participants of the research noted that various social formations produce quite a negative image of the teacher. The teacher’s homunculus, developed by these formations, is very limited, tired and an unreliable executor. Speaking of the homunculus created by the social agents of the school field, it is obvious that it is constructed based on the traditional notion of a teacher. The school’s administration, the parents, the pupils, the universities and institutes of higher education that prepare the teachers and the teachers themselves – they all impact the construction of the teacher’s homunculus in the school field. The teachers seem to be sure that they can be teachers only when they meet the standards of the homunculus. These “standards” are brought to them by the authorities – the school’s administration or the principal, for example. The informants that took part in this study believe that a large segment of principals, parents and pupils do not respect the teachers, doubt their professionalism and competency to do their jobs properly; they limit the work opportunities of the teachers. The distrust in teachers presents itself as control. The teachers who participated in this study usually do not agree with the homunculus that is constructed by the outside environment or the school field’s agents. They – the teachers – see the teacher as a character full of many positive qualities. The study showed what kind of homunculus is characteristic to the concept of the self shared by the informants. The informants, describing themselves as teachers, enumerated various traits and abilities that, in their opinion, create what is characteristic of the teachers’ image. They also listed the necessary requirements for teachers’ looks and behavior. The informants revealed that they have differing relationships with the teacher’s homunculus. A homunculus hides within one’s consciousness. These roles become inherent, and the breaking away or the failure to perform them well enough evoke frustration, reproaches or sanctions by the society, by means of which that same society attempts to get rid of the “bad actor.” In conclusion, we can state that the teacher’s homunculus is widely spread in Lithuania; it has not only taken over our consciousness, but it also the dictates professional behavior of the teachers, the attitudes of others toward teachers and the evaluation of that behavior. The focus on the homunculus does not let us understand that the teachers’ positions and dispositions are created by structures as well as agents, both from the outside and the inside.